PRICE DYNAMICS AND PRODUCT QUALITY IN FORMING PERFUME PURCHASE DECISIONS: A LITERATURE REVIEW STUDY - Willy Rapel Apentri Sitohang; Edwin Zusrony; Sri Murtini (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The rapid development of the perfume industry in Indonesia and the increasing competition between brands in luring consumers become the motivation of this study. In this respect, price and product quality are major variables in purchase decisions. This study attempts to evaluate the dynamics of price and product quality in determining the decision to buy perfume. The research used literature review method with descriptive qualitative methodology. The data were secondary data acquired from eleven relevant scientific journals, published in the 2023–2026 period. Data analysis consisted of identifying, selecting, appraising and synthesising prior study findings. The results show that the most dominant factor affecting the perfume purchasing decision is product quality, in particular through scent, durability, packaging, and product safety. Price is also a consideration in purchasing decisions as buyers weigh the benefits they will receive against the expenditures they will incur. Furthermore the supporting variables such as brand image, electronic word of mouth and online customer feedback, enhance the consumer choice making process. Therefore, product quality and pricing are the major criteria that influence the decision to buy perfume.